HUBUNGAN KEBIASAAN ANAK MENJAGA KESEHATAN DAN KEBERSIHAN GIGI DENGAN KARIES MOLAR PERTAMA PERMANEN PADA MURID SEKOLAH DASAR DI KECAMATAN PADANG TIMUR KOTA PADANG - Susi Susi; Didin Kustantiningtyastuti; Yona Ladyventini (Andalas Dental Journal, 2013)
Dental caries and gum disease (gingivitis) is a disease which are often found in elementary school’s student in Indonesia. One of the cause of the oral and dental problems is behavior factor or neglect of oral hygiene. This study aims to determine the relationship of children's behaviors to health and dental hygiene with caries incidence in permanent first molars in SDN 15 Eastern District of Padang. The design of this study is the Cross Sectional Study. The research was conducted at the Elementary School District 15 East Padang Padang Padang in January 2012. This study sample was a student of class IV, V, VI amounted to 80 people. The data was collected through questionnaires and dental examinations by chi-square analysis.